Right atrial thrombus in a patient with COVID-19 pneumonia: a case report. Issue Volume 4:Issue FI1(2020)Special Issue (4th September 2020) - Shamsah, Mohammed A; Bitar, Zouheir Ibrahim; Alfoudri, Huda
Abstract: Background: Significant coagulopathy and hyperinflammation are found in patients with coronavirus disease 2019 (COVID-19). Expert consensus has recommended prophylactic anticoagulation in COVID-19 patients due to the risk of thrombo-embolism. However, the use of therapeutic anticoagulation in these patients is still a matter of debate. Case summary: We describe a patient with COVID-19 pneumonia and a clinical hyperinflammatory state. He developed early respiratory depression and required ventilation, and he subsequently developed haemodynamic instability. Point-of-care echocardiography demonstrated a right atrial thrombus and right ventricular dysfunction suggestive of acute massive pulmonary embolism. He was managed with veno-arterial extracorporeal membrane oxygenation and local thrombolysis. Discussion: Critical cases of COVID-19 pneumonia are associated with hypercoagulation, and these patients should be monitored closely for complications. Therapeutic anticoagulation may play a role in the management and prevention of thrombo-embolism.